Chinese Private Preschool Teachers’ Teaching Readiness and Teacher–Child Relationships: The Chain Mediation Effects of Motivation to Teach and Self-Efficacy - Hui Li; Wei Chen; Huihua He; Wenwei Luo (Behavioral Sciences, 2023)
The teacher–child relationship is a key element in measuring the quality of childcare institutions and is essential to the current and future physical and mental developmental outcomes of children. The purpose of this study is to investigate the role of private preschool teachers’ readiness to teach in influencing the teacher–child relationship, and to explore the mechanisms by which teachers’ motivation and self-efficacy mediate their readiness to teach and the teacher–child relationship. Online questionnaires were administered to 289 early-childhood teachers in Shanghai, China. The findings of the study indicated a significant and positive correlation between early-childhood teachers’ readiness to teach and the quality of the teacher–child relationship. In addition, early-childhood teachers’ internal motivation to teach and self-efficacy mediated their readiness to teach and the teacher–child relationship, respectively. However, teachers’ external motivation did not mediate the effect of teaching readiness on the quality of the teacher–child relationship. Moreover, teachers’ motivation to teach (encompassing both internal and external factors) and their self-efficacy played chained roles in mediating the relationships between teaching readiness and the teacher–child relationship. This study highlights the significant roles of teaching readiness and instructional motivation, along with self-efficacy, in cultivating positive teacher–child relationships within early-childhood education settings.